Esports for the Youth: Fostering Skills and Empowering Minds - Danella Geneva (GoAcademica Research & Publishing, 2023)
Esports, short for electronic sports, has emerged as a rapidly growing phenomenon in recent years. This article aims to explore the impact of esports on the youth, focusing on its potential to cultivate essential skills and empower young minds. The study delves into the various aspects of esports, including its historical development, the rise of competitive gaming, and the educational benefits it offers. Through an analysis of existing literature and empirical evidence, this research sheds light on the positive implications of esports for the younger generation, emphasizing its potential to shape future leaders and problem solvers.